Scripting to enhance university students' critical thinking in flipped learning: implications of the delayed effect on science reading literacy. Issue 5 (4th July 2018) - Lee, Yuan-Hsuan
ABSTRACT: Premised on Web 2.0 technology, the current study investigated the effect of facilitating critical thinking using the Collaborative Questioning, Reading, Answering, and Checking (C-QRAC) collaboration script on university students' science reading literacy in flipped learning conditions. Participants were 85 Taiwanese university students recruited from two introductory educational psychology courses. Groups were formed by affinity grouping and were randomly assigned to collaborative learning conditions with or without C-QRAC script support. Both groups received direct introduction to critical thinking and were given the assigned reading before class. Results of the study showed that direct instruction on critical thinking may have an immediate effect on science reading literacy for both groups. Moreover, the effect of the C-QRAC collaboration script was contingent upon time, gender moderation, and test formats. Students who followed the C-QRAC script performed better on the delayed advanced multiple-choice items than those in the control group. Further, the C-QRAC script helped eliminate the gender gap in immediate and delayed total MC. But in delayed basic MC, males demonstrated higher scores than females. Higher prior knowledge predicted better scores on delayed basic MC as well as immediate and delayed constructed-response items. The findings imply that providing structure for university students in the flipped collaborative science reading had a sustained effect on their learning such that they were more likely to think about the questions discussed with partners, to try to find the answers to the questions, to discuss findings in the reading content with friends, or to reread the shared online note or article. As a result, we suggest use of the C-QRAC collaboration script to facilitate students' critical thinking and enhance their self-directed learning in flipped learning conditions.